Management accounting dynamics in Bangladesh: areas and factors behind the changes / Mohammad Rokibul Kabir - Kabir, Mohammad Rokibul (Accounting Research Institute (ARI) and UiTM Press, Universiti Teknologi MARA, Shah Alam, 2019)
Rapid growth in technologies and competitive business environments have brought significant changes in management accounting practices in the manufacturing industries. To cope with these changes a good number of management accounting tools have been developed in helping managerial decisions both at operating and strategic levels. Researchers have identified that the implementation of such tools in developed countries brought success in decision making though research in this particular area in less developed countries, especially in Bangladesh, is not significant yet. Thus, this research aimed to explain the changes that have taken place and the factors behind the changes in management accounting practices (MAP) in manufacturing industries. The listed manufacturing companies in Bangladesh consist of the population and sample of the study. Factor reduction techniques were used to analyze the influencing variables behind the changes in MAP. The paper reveals that the changes that have taken place from 2001 to 2010 period in MAP are mainly in the operational areas while after 2011 the changes in MAP have mostly taken place in the area of strategic decision making. The factors behind the changes are categorized under the heads of Changes in Business and Organization Strategy and Changes in Manufacturing and Information Technology by applying factor analysis.